Fiscal policies in federal states - Braun, Dietmar (Aldershot, England ; Burlington, VT : Ashgate, 2003)
This text investigates the impact of federal structure on fiscal policy-making in four country cases and answers the question to what extent federal structures hinder or, on the contrary, enhance a states' decision and co-ordination capacity in the field of fiscal policy. It questions the common assumption that federal structures restrain the co-ordination and hence macroeconomic management capacity.
Includes bibliographical references (p. [275]-285) and index.
rpm 29/08/16
Loans
Keywords: Fiscal policy; Intergovernmental fiscal relations; Federal government